Pengembangan Sistem Informasi Desa Terpadu Menggunakan Metode Rapid Application Development (RAD) Studi Kasus Desa Arjasa - Maulana Kevin Pradana; Anang Andrianto; Yudha Alif Auliya (Faculty of Computer Science, University of Jember, 2022)
Information systems are now an important part of a government agency. One of the government agencies that have used the information system is Arjasa Village. Arjasa Village has implemented a village service information system website that contains news, history, galleries, and certificate services. The village admin or operator in managing the village information system has several problems. The certificate service feature here is still less flexible in adding or making a certificate because it cannot move paragraphs, sentences, entries in the event of an error in position, and cannot change the certificate that has been printed by residents if there is an error in data entry. The historical feature is requested to be replaced with the village government information feature because it can be filled with village history, vision and mission, village profiles, institutions, and others related to village government. Then the village government wants the transparency feature of village funds or APBDes and features of population management. Therefore, the development of the Arjasa village information system is very necessary. In developing this system, the researcher uses the Rapid Application Development (RAD) method, because RAD is a method used in system development to overcome a condition where the development process uses a short and fast development cycle because the process is divided into several components. that can be reused, so that the developed system can find out the results without waiting a long time. RAD is also very suitable for small scale system development as in this case.